2018
DOI: 10.1007/s00705-018-3878-7
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of Polio-like Enterovirus C strains with differential clustering of CVA-13 and EV-C99 subgenotypes in a cohort of Malawian children

Abstract: Enteroviruses (EVs) are among the most commonly detected viruses infecting humans worldwide. Although the prevalence of EVs is widely studied, the status of EV prevalence in sub-Saharan Africa remains largely unknown. The objective of our present study was therefore to increase our knowledge on EV circulation in sub-Saharan Africa. We obtained 749 fecal samples from a cross-sectional study conducted on Malawian children aged 6 to 60 months. We tested the samples for the presence of EVs using real time PCR, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(52 citation statements)
references
References 56 publications
9
42
0
Order By: Relevance
“…This epidemiological information on the genetic diversity of EV contributes to the growing knowledge of genotypes circulating in Ethiopia. Most of the genotypes detected in this study were reported from previous studies in Ethiopia and other sub‐Saharan African countries 19‐24 . The frequent detection of EV‐B and EV‐C in this study is comparable with a previous study in Ethiopia in 2016 19 .…”
Section: Discussionsupporting
confidence: 89%
“…This epidemiological information on the genetic diversity of EV contributes to the growing knowledge of genotypes circulating in Ethiopia. Most of the genotypes detected in this study were reported from previous studies in Ethiopia and other sub‐Saharan African countries 19‐24 . The frequent detection of EV‐B and EV‐C in this study is comparable with a previous study in Ethiopia in 2016 19 .…”
Section: Discussionsupporting
confidence: 89%
“…In the context of global eradication of polioviruses, information on NPEVs circulation is key to understand their role in AFP context. Surveillance data shows that in Europe, USA and Africa, most cases have been associated with EV-B species, whereas species A are normally more prevalent in Asia [13][14][15][16][17]. The etiology of AFP cases in Brazil is systematically determined, although information on molecular diversity and NPEV circulation patterns is still scarce [18].…”
Section: Introductionmentioning
confidence: 99%
“…Within this species, CVA20 and EV-C99 were the most common serotypes identified in our cohort. Although both serotypes have been isolated from AFP patients, they have been more commonly identified in apparently healthy individuals [23,25,43,48]. In our cohort, all but one of the HIV-positive individuals infected with these serotypes had a CD4+ T cell count higher than 200 cells/µL.…”
Section: Discussionmentioning
confidence: 68%
“…In our study, the majority of strains were assigned to Enterovirus C (29/39), which is often described as the most common group circulating in sub-Saharan Africa [43,47]. Within this species, CVA20 and EV-C99 were the most common serotypes identified in our cohort.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation